The Knowledge of the Security Unit (Satpam) about Basic Life Support in Ruteng City, East Nusa Tenggara - Yuliana Reginaldis Rosali Krowa; Lusia Henny Mariati; Paskaliana Hilpriska Danal (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Background: Cardiac arrest is an emergency condition that often occurs outside the hospital. Knowledge of Basic Life Support (BLS) and techniques for performing cardiopulmonary resuscitation can improve patient survival until medical assistance arrives, this can sustain a patient's life in many cases. Ordinary and trained lay people, including security guards, need to be alert when helping victims by providing basic life support in order to increase the survival of sufferers, but the failure of efforts to save victims is due to BLS actions that are not in accordance with procedures. Methods: This research is a quantitative research with a descriptive approach with a sample of 75 security guards working in Ruteng City. Results: The results of the analysis of this study show that most of the security guards in Ruteng City, namely 77% (58 people) have poor knowledge about BLS, 16% have sufficient knowledge about BLS, and only 7% have good knowledge about BLS. Suggestion: Security guards must receive periodic training on Basic Life Support, this is done to reduce the mortality rate of cardiac arrest victims outside the hospital.